Why Can’t We Learn Foreign Languages in Turkey? Some Psychological Reasons Behind It - Yiğit, Ecenaz; Keser, Ömer Faruk; Uzun, Levent (International Dialogues on Education Journal, 2020)
Foreign language learning is one of the most significant endeavours for people in all countries in the world. Turkey has given importance to foreign language learning for years. Nevertheless, it has been an unresolved problem for Turkish people. The purpose of the present study is to determine why people fail to learn foreign languages in Turkey and the psychological reasons behind it by focussing on perception, foreign language anxiety and learned helplessness. The participants were 100 volunteer students (56 female, 44 male) who were selected randomly from different faculties and departments at Bursa Uludag University. The data were collected from a questionnaire, which consisted of five main sections to identify participants’ background, perception of foreign language learning, level of foreign language anxiety, and level of learned helplessness. Both quantitative and qualitative data were collected. The data were analysed in relation to the research questions that guided the study. The results indicated that the participants’ perceptions of foreign language learning were positive owing to past positive experiences, but their level of foreign language anxiety was high due to lack of practice in language skills in the past; and their level of learned helplessness was low because of the positive perceptions they possessed. In addition, the findings suggested that the four language skills should be taken into consideration when the contents of foreign language lessons at schools and foreign language courses at universities are prepared and determined.